Evidence for marked underutilization of insurance billing in malignant pleural mesothelioma in Finland - Torkki Paulus; Paajanen Juuso; Kytö Ville; Laaksonen Sanna; Räsänen Jari; Myllärniemi Marjukka; Ilonen Ilkka (Australia, 2022)
Background
Substantial variation in health care costs for malignant pleural mesothelioma (MPM) has previously been identified.
Materials and Methods
We analyzed the changes in health care costs in MPM in Finland during 2002–2012. Finland has low-threshold public health care and a mandatory Workers' Compensation scheme that covers all occupational-related disease expenses. The costs include treatment costs for inpatients, hospice care, medication costs, rehabilitation costs, and travel costs. All costs are expressed in 2012 prices, adjusted using the consumer price index.
Results
A total of 907 MPM patients were included in the study. Mean duration of inpatient episodes increased 7% per year from 2002 to 2012, correlating with total costs (R2 = 0.861, p < 0.05). The annual total costs for treatment increased from 1.7 to 4.3 m€ during the study period and the cost per patient from 27 000 to 43 000 €. The overall costs increased progressively by the number of procedures performed. In patients who had been compensated for occupational cause by Workers' Compensation Center, only 36% of the overall care costs were billed from the insurance company. Billing of inpatient costs was 86% in these patients.
Conclusion
During the study period, we found that the costs of MPM increased more than the average health care costs. This may be because of advanced diagnostic workup or more costly treatment (e.g., pemetrexed). Moreover, only one-third of all health care costs are charged to Workers' Compensation Insurance.